Walk, jog, run : a free-motion quilting workout :muscle-memory-building exercises, projects & tips - Tomasson, Dara, 1973- (Stash Books, an imprint of C&T Publishing, 2020)
"Free-motion quilting book how to get started and 10 projects"--